Key Trends and Results of Kazakhstan’s foreign economic cooperation with the EAEU Countries - V. Yu. Dodonov (Проблемы постсоветского пространства)
Five full years of the functioning of the Eurasian Economic Union (EAEU) provide an opportunity to highlight the main trends of cooperation under this association and to summarize some of their results. The article discusses the trends and results of Kazakhstan’s foreign economic cooperation with the EAEU countries in the main areas, including mutual trade, mutual investments, as well as some others. The analysis revealed that in most areas of cooperation between Kazakhstan and the EAEU countries during the period of the union’s existence, leading dynamics were observed, which indicates the positive results for the national economy of the first five years of operation as part of the integration association.